Impact of Early Childhood Malnutrition on Adult Brain Function: An Evoked-Related Potentials Study - Roger, Kassandra; Vannasing, Phetsamone; Tremblay, Julie; Bringas Vega, Maria L.; Bryce, Cyralene P.; Rabinowitz, Arielle G.; Valdés-Sosa, Pedro A.; Galler, Janina R.; Gallagher, Anne (Frontiers in Human Neuroscience, 2022)
More than two hundred million children under the age of five years are affected by malnutrition worldwide according to the World Health Organization. The Barbados Nutrition Study (BNS) is a 55-year longitudinal study on a Barbadian cohort with histories of moderate to severe protein-energy malnutrition (PEM) limited to the first year of life and a healthy comparison group. Using quantitative electroencephalography (EEG), differences in brain function during childhood (lower alpha1 activity and higher theta, alpha2 and beta activity) have previously been highlighted between participants who suffered from early PEM and controls. In order to determine whether similar differences persisted into adulthood, our current study used recordings obtained during a Go-No-Go task in a subsample of the original BNS cohort (population size (N)=53) at ages 45-51 years. We found that previously malnourished adults (sample size (n)=24) had a higher rate of omission errors on the task relative to controls (n=29). Evoked-Related Potentials (ERP) were significantly different in participants with histories of early PEM, who presented with lower N2 amplitudes. These findings are typically associated with impaired conflict monitoring and/or attention deficits and may therefore be linked to the attentional and executive function deficits that have been previously reported in this cohort in childhood and again in middle adulthood.